2015
DOI: 10.1371/journal.pone.0129233
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CREB3L1 as a Biomarker Predicting Doxorubicin Treatment Outcome

Abstract: BackgroundDoxorubicin has been shown to inhibit proliferation of cancer cells through proteolytic activation of CREB3L1 (cAMP response element binding protein 3-like 1), a transcription factor synthesized as a membrane-bound precursor. Upon doxorubicin treatment, CREB3L1 is cleaved so that the N-terminal domain of the protein can reach the nucleus where it activates transcription of genes that inhibit cell proliferation. These results suggest that the level of CREB3L1 in cancer cells may determine their sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…As doxorubicin was only effective in blocking cell proliferation in CREB3L1-expressing cells, this suggests that only patients expressing CREB3L1 are likely to benefit from doxorubicin treatment. In support of this idea, a recent report showed that higher levels of CREB3L1 expression strongly inversely correlated with tumor volume upon doxorubicin treatment in renal cell carcinoma xenografts ( r = −0.891; p = 0.017) [ 22 ], leading to the suggestion that CREB3L1 could be a biomarker that predicts doxorubicin treatment outcome. These results also suggest that the loss of CREB3L1 may contribute to doxorubicin treatment resistance.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As doxorubicin was only effective in blocking cell proliferation in CREB3L1-expressing cells, this suggests that only patients expressing CREB3L1 are likely to benefit from doxorubicin treatment. In support of this idea, a recent report showed that higher levels of CREB3L1 expression strongly inversely correlated with tumor volume upon doxorubicin treatment in renal cell carcinoma xenografts ( r = −0.891; p = 0.017) [ 22 ], leading to the suggestion that CREB3L1 could be a biomarker that predicts doxorubicin treatment outcome. These results also suggest that the loss of CREB3L1 may contribute to doxorubicin treatment resistance.…”
Section: Discussionmentioning
confidence: 94%
“…Epigenetic downregulation of CREB3L1 mRNA expression by DNA methylation is associated with increased tumor grade and aggressive phenotype in bladder cancer [ 20 ]. Also, CREB3L1 has been shown to be necessary for the chemotherapeutic drug doxorubicin to block cell proliferation and may function as a biomarker in predicting response to therapy [ 21 , 22 ]. Doxorubicin increases ceramide production, which in turn stimulates regulated intramembrane proteolysis of CREB3L1 to its mature active form.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of Nr4a1 as a transcription factor of the Creb3l1 gene may have importance in cancer research. The expression levels of Nr4a1 and Creb3l1 have been used a biomarkers to grade cancerous cells/tumors (Alexopoulou et al, 2010 ; Rose et al, 2014 ; Safe et al, 2014 ; Denard et al, 2015 ; Ward et al, 2016 ). No connection has currently been made between Nr4a1 and Creb3l1 expression in cancer cells, but there are studies that support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…CREB3L1 is a transcription factor that regulates the expression of many genes, including ER chaperones such as GRP78 42 . Several pieces of evidence have demonstrated the loss of CREB3L1 expression in malignant cancer cells and that the maintenance of CREB3L1 expression could potentially suppress tumorigenesis 16 42 . The bioinformatics analysis and luciferase assays showed that CREB3L1 is a bonafide target of miR-146a during HUVEC angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CREB3L1 (cAMP responsive element-binding protein 3-like 1; also known as OASIS) is a member of the CREB3b ZIP transcription factor subfamily and was first identified in long-term cultured astrocytes and gliotic tissue 13 . CREB3L1 functions as a transcription factor that regulates target genes with important functions in many physiological processes 14 15 16 . Interestingly, CREB3L1 is down regulated in bladder cancer and acts as a tumor suppressor by directly suppressing tumor cell migration and colony formation 17 .…”
mentioning
confidence: 99%